Pembrolizumab combined with surgical treatment for spontaneously ruptured undifferentiated pleomorphic sarcoma of the liver: a case report and literature review - He, Tao; Ke, Sun; Zou, Jieyu (Frontiers in Immunology, 2025)
Undifferentiated pleomorphic sarcoma of the liver (UPSL) is a rare pathological type characterized by an undefined mechanism, low incidence, high metastatic rate, aggressive behavior, and an inferior prognosis; no standardized treatment protocols or guidelines currently exist. This article reports the case of an 83-year-old male with UPSL confirmed through surgical resection and pathological biopsy. Postoperatively, he received eight cycles of pembrolizumab, which resulted in a favorable clinical efficacy. With advances in medical technology, the integration of surgery and immunotherapy is expected to play an essential role in treating this rare disease and monitoring its prognosis.